Philosophical study of growth and development orthodontics: Studi filosofis tentang pertumbuhan dan perkembangan ortodontik - Eka Erwansyah; Eddy Heriyanto Habar; Rasmidar Samad; Burhanuddin Daeng Pasiga; Fuad Husain Akbar; Andi Kurniati (Makassar Dental Journal, 2021)
A thorough knowledge of dentocraniofacial growth and development is necessary for every dentist. From philosophies stand point, the ontology of to comprehend condition observed understanding the growth and development processes that orthodon-tics. Meanwhile epistemology, methods of studying about growth and development in orthodontic treatment has progressed a lot. Axiologically, dentists and orthodontists are heavily involved in the development of not just the dentition but the entire den-tofacial complex, a practitioner may be able to manipulate facial growth for the benefit of the patient and malocclusion treat-ment. It is not possible to do so without a thorough understanding of both the pattern of normal growth and the mechanism that underlie it.